Reflections on the Cascade Model for Teacher Professional Development: A Case Study of RSC-Yusuf Hamied Inspirational Chemistry Programme in India - Ladage, Prof. Savita; George, Hanza; Chunawala, Sugra (Voices of Teachers and Teacher Educators, 2021)
The RSC-Yusuf Hamied Inspirational Chemistry Programme was launched in India in 2014 by the Royal Society of Chemistry (RSC, UK). A component of this programme was the professional development of about 8,000 chemistry teachers across India, in five years. This paper reports on an evaluation study conducted in 2018, that reflects on the implementation of the RSC teacher professional development (TPD) programme, via a cascade model. Our analysis of the RSC-TPD programme involved the use of multiple levels of evaluation proposed by Guskey. This study involves data collection from 32 government/ government aided schools in three states of India. The findings present some evidence of the impact of the programme and highlight the need for sustained interactions with teachers.